Ortoll, S., y Preciado, J. (Eds.) (2016). ¿Por Dios opor la Mitra? Obispos, cristeros, evangélicos,1926–1992. El Colegio de Jalisco. 150 pp. - Rodríguez Mayoral, Alejandro (Letras Históricas E-ISSN: 2448-8372, 2020)
Reseña de libro.